Application of Reciprocal Style to Improve Learning Outcomes of Manipulative Movements and Responsible Attitudes in Grade IV of SD Negeri Sungai Putting - Pradana, Erick Febrian; Mashud, Mashud (PENJAGA : Pendidikan Jasmani dan Olahraga, 2026)
This study aims to improve the learning outcomes of manipulative movements through the application of Reciprocal Teaching Style and Responsible Attitude in grade IV of SD Negeri Sungai Puting. The research method uses the Kemmis and McTaggart model Class Action Research (PTK) which consists of two cycles, including the stages of planning, action, observation, and reflection. The subjects of the study were 18 students. The data collection instrument uses practical tests, observation sheets. The results showed a significant increase in each cycle. The completeness of learning in the pre-cycle on skills was 16.7%, and for responsible attitudes 52.6% increased to 44.4% for skills and responsible attitudes to 83% in cycle I, and in cycle II a significant increase occurred in skills by 89.9% and for responsible attitudes 100%. The increase in students' manipulative movement learning outcomes increased from the low category in the pre-cycle to the very high category in the second cycle. In conclusion, the application of the Reciprocal teaching style through the stages of understanding, applying, and reflecting combined with game variations and adjustments to throwing distance in Cycle II proved effective and successfully achieved the success indicators of the research. This process not only improves the physical (psychomotor) skills of grade IV students in manipulative movements, but also optimally builds responsible character and their confidence in learning